2021
DOI: 10.1098/rsbl.2020.0780
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance governed by gut symbiosis in a rice pest, Cletus punctiger, under laboratory conditions

Abstract: Resistance to toxins in insects is generally thought of as their own genetic trait, but recent studies have revealed that gut microorganisms could mediate resistance by detoxifying phytotoxins and man-made insecticides. By laboratory experiments, we here discovered a striking example of gut symbiont-mediated insecticide resistance in a serious rice pest, Cletus punctiger . The rice bug horizontally acquired fenitrothion-degrading Burkholderia through oral infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Results of this study demonstrated that a rice bug effectively degraded organophosphate fenitrothion by Burkholderia bacterial specie via oral infection and stayed it in the midgut part of the rice bug. The degradation of fenitrothion by the isolating bacterial species from the midgut revealed that gut microbiomes are highly capable of degrading pesticides in insects, and insect gut symbiosis plays a significant role in the development of resistance against fenitrothion in the host rice bug ( Ishigami et al, 2021 ). In another study, the resistance of stored grain products against phosphine fumigation was studied.…”
Section: Functions Of Insect Gut Microbiotamentioning
confidence: 99%
“…Results of this study demonstrated that a rice bug effectively degraded organophosphate fenitrothion by Burkholderia bacterial specie via oral infection and stayed it in the midgut part of the rice bug. The degradation of fenitrothion by the isolating bacterial species from the midgut revealed that gut microbiomes are highly capable of degrading pesticides in insects, and insect gut symbiosis plays a significant role in the development of resistance against fenitrothion in the host rice bug ( Ishigami et al, 2021 ). In another study, the resistance of stored grain products against phosphine fumigation was studied.…”
Section: Functions Of Insect Gut Microbiotamentioning
confidence: 99%
“…In this context, the insect gut microbiome plays a central role in adaptation to novel host plants as it is of crucial importance for the complex interactions with insect metabolic pathways, which ultimately affect insect fitness (Hammer & Bowers, 2015; Zilber‐Rosenberg & Rosenberg, 2008). The gut microbiome of phytophagous insects can help to (1) break down the complex polysaccharides of the host plant cell wall, and (2) supplement nitrogen, vitamins, and sterols to nutritionally poor diets (Ben‐Yosef et al, 2010, 2014; Douglas, 2009), and (3) detoxify host plant allelochemicals (Hammer & Bowers, 2015) and insecticides (Ishigami et al, 2021; Kikuchi et al, 2012). For example, the symbiotic bacterium “ Candidatus Erwinia dacicola” is essential for the metabolism of larvae of the olive fly Bactrocera oleae (Rossi, 1790) (Diptera, Tephritidae) as it allows them to feed on unripe olives rich in allelochemicals (Ben‐Yosef et al, 2015; Pavlidi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Members of other gut microbiomes can also degrade insecticides in vitro . For example, degradation test revealed that the gut-colonizing Burkholderia retains a high degrading activity of the organophosphate compound in the gut of rice bug Cletus punctiger ( Ishigami et al., 2021 ). A gut bacteria Lactobacillus plantarum was shown to metabolize organophosphate insecticide chlorpyrifos and may be beneficial to reducing chlorpyrifos toxicity in Drosophila melanogaster ( Daisley et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%